KESIAPAN ORANG TUA MENGAJARKAN LITERASI DIGITAL PADA ANAK 5-6 TAHUN DI TK PAUD TERPADU - Khotimah, Hikmah Husnul; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
This research aims to describe the readiness of parents in teaching digital literacy to children aged 5-6 years at the TK PAUD Terpadu west Pontianak. The research method used is a descriptive method in the form of qualitative research. The subjects in this research were 10 parents and 2 teachers in the 5-6 year age group at the TK PAUD Terpadu West Pontianak. The data collection techniques used in this research were questionnaires, interviews and documentation. The results of the research show that: parents' readiness in teaching digital literacy covers several aspects with percentages, namely parents' readiness in the motivation aspect to support the development of digital literacy of 84.36%, parents' readiness in the cognitive aspect regarding knowledge in the development of digital literacy of 84. .67%, and parents' readiness in operational aspects to fulfill children's needs for digital literacy development is 86%. Based on the results of this percentage, it shows that parents have an interpretation in the very ready category in teaching digital literacy to children aged 5-6 years in TK PAUD Terpadu West Pontianak